"It really does not matter to me, they can be two purple unicorns": Barriers and facilitators to sexual orientation and gender identity (SOGI) measurement in the NCI Community Oncology Research Program (NCORP). Issue 28 (1st October 2022) - Mullins, Megan A; Rankin, Aaron; Washington, Ariel; Stasenko, Marina; Friese, Christopher Ryan; Cooley, Mary E.; Hudson, Matthew F.; Wallner, Lauren P.
Abstract : 170 Background: Despite recommendations from numerous clinical bodies (e.g., ASCO), less than 20% of NCORP-affiliated practices regularly collect SOGI data. This gap compromises the ability to identify and correct care inequities experienced by sexual and gender minority (SGM) individuals. Therefore, we evaluated provider- and clinic- level barriers and facilitators to SOGI collection at NCORP practices across the US. Methods: We conducted 14 interviews across seven NCORP oncology practices via Zoom. We purposefully sampled to ensure geographic, racial, and ethnic diversity of patient populations. We interviewed one clinician (oncologist, advanced practice provider) and one clinic staff member per practice. The Consolidated Framework for Implementation Research (CFIR) informed thematic analysis that identified barriers and facilitators to SOGI data collection. Interviews were recorded, transcribed, and coded by two coders who adjudicated any discordance. Analyses were conducted in NVivo. Results: Thematic saturation occurred after interviews at six practices, with interviews at the seventh practice confirming saturation. Participants represented five geographic regions and included three Minority Underserved practices and two rural practices. Several organizational context characteristics influenced SOGI data collection: access to knowledge, information technology infrastructure, staff processes, and perceived relative priority of SOGI for an oncology visit. All oncologists expressed a low relative priority of sexual orientation data for oncology care. Gender identity had higher priority because it influences how clinicians should address patients. At the clinic level, this low relative priority coincides with a lack of processes and policies for collecting SOGI from all patients. At the oncology care team level, perceived irrelevance to oncology care was related to discomfort in asking SOGI, fear of patient discomfort, and limited awareness of SOGI in electronic health records. Suggested solutions included: normalizing asking SOGI questions, giving patients privacy to complete SOGI, and clarifying relevance of SOGI for clinical purposes. Understanding how SOGI improves patient experiences was a facilitator for collection. Conclusions: Within this NCORP practice sample, SOGI data collection barriers included clinician-perceived low relative priority for collection, and perceptions that SOGI disclosure does not influence care quality, despite most interviewees expressing a strong desire to show respect to patients and provide high quality cancer care. Oncology teams may benefit from training on culturally sensitive SOGI collection, education on SOGI data relevance to oncology practices, and support for implementing SOGI data collection policies.